Association between glycaemic control and common infections in people with Type 2 diabetes: a cohort study. Issue 4 (22nd September 2016) - Hine, J. L.; de Lusignan, S.; Burleigh, D.; Pathirannehelage, S.; McGovern, A.; Gatenby, P.; Jones, S.; Jiang, D.; Williams, J.; Elliot, A. J.; Smith, G. E.; Brownrigg, J.; et al.
Abstract: Aim: To investigate the impact of glycaemic control on infection incidence in people with Type 2 diabetes. Methods: We compared infection rates during 2014 in people with Type 2 diabetes and people without diabetes in a large primary care cohort in the UK (the Royal College of General Practitioners Research and Surveillance Centre database). We performed multilevel logistic regression to investigate the impact of Type 2 diabetes on presentation with infection, and the effect of glycaemic control on presentation with upper respiratory tract infections, bronchitis, influenza‐like illness, pneumonia, intestinal infectious diseases, herpes simplex, skin and soft tissue infections, urinary tract infections, and genital and perineal infections. People with Type 2 diabetes were stratified by good [HbA1c < 53 mmol/mol (< 7%)], moderate [HbA1c 53–69 mmol/mol (7–8.5%)] and poor [HbA1c > 69 mmol/mol (> 8.5%)] glycaemic control using their most recent HbA1c concentration. Infection incidence was adjusted for important sociodemographic factors and patient comorbidities. Results: We identified 34 278 people with Type 2 diabetes and 613 052 people without diabetes for comparison. The incidence of infections was higher in people with Type 2 diabetes for all infections except herpes simplex. Worsening glycaemic control was associated with increased incidence of bronchitis, pneumonia, skin and soft tissue infections, urinary tract infections, and genital and perineal infections, but not with upper respiratory tract infections, influenza‐like illness, intestinal infectious diseases or herpes simplex. Conclusions: Almost all infections analysed were more common in people with Type 2 diabetes. Infections that are most commonly of bacterial, fungal or yeast origin were more frequent in people with worse glycaemic control. What's new?: This is the first large‐scale study of the impact of glycaemic control on the incidence of infection across a wide range of conditions, with adjustment for important confounders. Worse glycaemic control was associated with greater risk of conditions that are most commonly of bacterial, fungal or yeast origin, but not of those of viral origin (with the exception of bronchitis).